Konsep Bermain Dalam Pendidikan Anak Usia Dini Menurut Pemikiran Imam Ghazali: Implikasi Terhadap Pengembangan Karakter Dan Spiritual - Ade Ismail Fahmi; Rini Novianti Yusuf; Gina Kania; Anwar Musyaddat; Ernawati Ernawati (Departement of Mathematics Education, 2024)
Play in early childhood education has a very important role, not only as a recreational activity, but also as a means of character formation and spiritual development of children. Imam Ghazali, a great scholar, expressed his views on the importance of play in children's education, where play can be a medium for instilling moral and spiritual values. This research aims to dig deeper into the concept of play according to Imam Ghazali and its implications for the development of character and spirituality in early childhood. The research method used is a qualitative approach with literature study, where data is obtained through analysis of literature related to Imam Ghazali's thoughts as well as relevant previous research. Data were analyzed descriptively to describe the concept of play and its application in the context of early childhood education. The research results show that Imam Ghazali views play as an activity that teaches moral values, such as honesty, responsibility and empathy, as well as introducing spiritual values in children's lives. Playing can be an effective means of shaping children's character and deepening their understanding of religious teachings. The implication of this research is the importance of integrating the concept of play in the early childhood education curriculum which prioritizes children's character and spiritual development. Education that combines these two aspects can create children who are not only intellectually intelligent, but also have noble character.